# X^2+6x-27=0

## Simple and best practice solution for X^2+6x-27=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for X^2+6x-27=0 equation:

Simplifying
X2 + 6x + -27 = 0

Reorder the terms:
-27 + X2 + 6x = 0

Solving
-27 + X2 + 6x = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '27' to each side of the equation.
-27 + X2 + 27 + 6x = 0 + 27

Reorder the terms:
-27 + 27 + X2 + 6x = 0 + 27

Combine like terms: -27 + 27 = 0
0 + X2 + 6x = 0 + 27
X2 + 6x = 0 + 27

Combine like terms: 0 + 27 = 27
X2 + 6x = 27

Add '-6x' to each side of the equation.
X2 + 6x + -6x = 27 + -6x

Combine like terms: 6x + -6x = 0
X2 + 0 = 27 + -6x
X2 = 27 + -6x

Simplifying
X2 = 27 + -6x

Reorder the terms:
-27 + X2 + 6x = 27 + -6x + -27 + 6x

Reorder the terms:
-27 + X2 + 6x = 27 + -27 + -6x + 6x

Combine like terms: 27 + -27 = 0
-27 + X2 + 6x = 0 + -6x + 6x
-27 + X2 + 6x = -6x + 6x

Combine like terms: -6x + 6x = 0
-27 + X2 + 6x = 0

The solution to this equation could not be determined.`